Natural versus artificial anatomy in science education: Visual supports and technological innovations - Sánchez-Ortiz, Alicia; Sterp Moga, Emanuel; Hernández-Muñoz, Óscar (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
In this paper, we carry out a historiographical review of the manufacture of artificial anatomies that were widely demanded as didactic tools in the teaching of nature, between the late eighteenth and early twentieth centuries. We analyse the educational and social contexts that favoured the wide diffusion of this type of artefacts in the trade of scientific culture and describe the manufacturing techniques. The conclusion is that these artefacts, the fruit of human ingenuity, are material sources of extraordinary value for understanding the construction and evolution of science, advances in pedagogical resources and technological innovations.